The Relationship Between Workers' Knowledge and Attitudes Towards the Use of Personal Protective Equipment (PPE) and the Incidence of Work Accidents in Production Workers of PT Inka (Persero) Madiun - Lutfi Nur Fadhilah; Zaenal Abidin; Retno Widiarini (CV. Syntax Corporation Indonesia, 2024)
Occupational safety and health (OHS) is one of the company's maintenance programs. The implementation of OHS programs for employees is very important to create an OHS system that includes elements of management, employment and working conditions and an integrated work environment. The purpose of this study was to analyze the relationship between workers' knowledge and attitudes towards the use of Personal Protective Equipment (PPE) with the incidence of work accidents in PT INKA (Persero) Madiun production workers. This study used a cross-sectional design with a quantitative approach. The population in this study were all production workers of assembly PT INKA (Persero) Madiun. The sample was taken using simple random sampling technique, with a sample size of 68 respondents. Data collection was done through questionnaires. Data analysis using the Chi-square test. Analysis result show that there is a relationship between the independent variables, namely knowledge (p-value = 0,003) and attitude (p-value = 0,001) and the dependent variable of work accidents. The conclusion in this study is that there is a significant relationship between knowledge and attitudes towards the use of PPE with the incidence of work accidents. Suggestions are expected that workers have high awareness and discipline in the behavior of using PPE so as to reduce the occurrence of work accidents.